Evaluation of Diagnostic Performance of Severe Acute Respiratory Syndrome Coronavirus 2-Specific Differential Principles Antibody Tests - Dinç, Harika Öykü; Gareayaghi, Nesrin; Özbey, Doğukan; Daşdemir, Ferhat; Akçin, Rüveyda; Sirekbasan, Serhat; Demirci, Mehmet; Saltoğlu, Neşe; Kocazeybek, Bekir S. (Cerrahpaşa Medical Journal, 2023)
Objective: We aimed to evaluate the diagnostic performance of tests based on enzyme-linked immunosorbent assay, chemiluminescent microparticle immunoassay, and lateral flow assay methods for detecting severe acute respiratory syndrome coronavirus 2 immunoglobulin G with serum samples of people who received the severe acute respiratory syndrome coronavirus 2 vaccine or have been previously infected. Methods: The serum samples were taken 28 days after were CoronaVac vaccine, BNT162b2 vaccine, or diagnosed with coronavirus disease 2019, were included in the study (n = 100). Neutralizing antibodies against the receptor-binding region of the spike protein S1 subunit of severe acute respiratory syndrome coronavirus 2, with antibody tests against 3 different principles (chemiluminescent microparticle immunoassay, enzyme-linked immunosorbent assay, lateral flow assay) (ARCHITECT IgG II Quant test, Abbott, USA/SARS-CoV-2 NeutraLISA, Euroimmun, Lübeck, Germany/ NeutraXpressTM, JOYSBIO Biotechnology Co. Ltd., Tianjin China) were studied. Statistical Package for Social Sciences v21 package program (IBM Corp., Armonk, NY, USA) was used for the statistical evaluation of the data. Results: When the surrogate neutralizing antibody enzyme-linked immunosorbent assay was compared with the lateral flow assay neutralizing anti- body test, the sensitivity was 74.7% and the specificity was 84%. In the lateral flow assay binding antibody test, the sensitivity was 93.3% and the specificity was 80%. When the chemiluminescent microparticle immunoassay was compared with the lateral flow assay neutralizing antibody test, the sensitivity was 63.2% and the specificity was 100%. In the lateral flow assay binding antibody test, the sensitivity was 78.9% and the specificity was 100%. Conclusion: According to our study, the diagnostic performance of lateral flow assay-based tests was not satisfactory. However, we think that tests with high sensitivity and specificity and compatible with plaque reduction neutralization test should be preferred in the evaluation of humoral immune response by immunological methods. Cite this article as: Dinç HÖ, Gareayaghi N, Özbey D, et al. Evaluation of diagnostic performance of severe acute respiratory syndrome coronavirus 2-specific differential principles antibody tests. Cerrahpaşa Med J. 2023;47(2):211-214.